ANALISIS SEMIOTIKA ROLAND BARTHES DALAM VIDEO MUSIK BTS INTERLUDE : SHADOW DAN OUTRO : EGO - Wahyu Natalia; Wulan Nurul (Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Mental health issues are still underestimated and stigmatized in the society. BTS music video Interlude: Shadow and Outro: Ego was inspired by C. G. Jung’s map of the soul. The goal of this theory is to reach individuation. Writer will use interpretive paradigm, a qualitative approach with Roland Barthes semiotic analysis. Writer uses C. G. Jung’s theory of individuation to support the analysis. The purpose of this research is to determine denotative, connotative, and the individuation process in BTS video music Interlude: Shadow and Outro: Ego. Data collected with visual material techniques and literature study. Data validation with data triangulation. The result of this research show that the individuation process in Interlude: Shadow, the ego integrates with the shadows, while in Outro: Ego, the ego that has been accepting shadow makes a dynamic connection with The Self. Individuation is increasingly achieved in the Outro: Ego music video.